NMR localization of the O‐mycoloylation on PorH, a channel forming peptide from Corynebacterium glutamicum. Issue 22 (4th October 2013) - Rath, Parthasarathi; Saurel, Olivier; Tropis, Maryelle; Daffé, Mamadou; Demange, Pascal; Milon, Alain
Abstract : PorH and PorA are two small peptides that, in complex, form a voltage‐dependent ion channel in the outer membrane of Corynebacterium glutamicum . Specific post‐translational modifications on PorA and PorH are required for the formation of a functional ion channel. The assignment of PorH proton NMR chemical shifts in DMSO, allowed identifying unambiguously the exact position of the PorH O‐mycoloylation on Ser 56 side chain. This was further confirmed by site directed mutagenesis and mass spectrometry. Together with the previously published localization of PorA mycoloylation, this provides the complete primary structure characterization of this outer membrane porin. Abstract : The PorA–PorH complex forms an ion channel in C. glutamicum outer membrane. Assignment of 15 N labelled PorH was obtained in DMSO. A specific shift on PorH Ser56 Hβ resonances revealed its O‐acylation. The O‐mycoloylation position was confirmed by mutagenesis and MALDI‐TOF MS.